Designing reliable silicone elastomers for high-temperature applications. (November 2018) - Ogliani, Elisa; Yu, Liyun; Mazurek, Piotr; Skov, Anne L.
Abstract: Reliability and durability are strict requirements for silicone elastomers employed in high-temperature applications, if long-time device performance is desired. Improving the thermal stability of silicone elastomers is a major challenge, addressed by both the scientific and the industrial community. Nevertheless, traditional methods such as adding heat-resistant fillers or chemical modifications still suffer from considerable shortcomings. Here, it is demonstrated that the thermal degradation behavior of silicone elastomers is affected strongly by network reactant stoichiometry. Comparative thermal degradation studies were performed on silicone elastomers synthesized with different stoichiometric ratios—and thereby different fractions of elastic, dangling, and sol structures. With the reported findings, we demonstrate how to optimize the stoichiometric ratio used to prepare silicone elastomers, in order to enhance their thermal stability by simple means in high-temperature applications. Graphical abstract: Highlights: Silicone elastomers with varying cross-linking densities were investigated through thermogravimetric analysis. Network reactant stoichiometry was shown to strongly affect thermal degradation behavior. Silicone polymers within the elastomer degrade thermally hierarchically, with most mobile polymers degrading the first. Removal of the sol fraction therefore leads to an overall increase in the thermal stability.